Tourism development and land rent. High-land vineyards road and solar train in Quebrada de Humahuaca (Jujuy, Argentina) - Braticevic, Sergio (2025)
This article presents a case study that relates tourism development to the category of “land rent”. In particular, the target area has undergone a process of increasing real estate appreciation since 2003, when it was declared a heritage site by UNESCO. This phenomenon came to a halt a decade later, due to the exhaustion of the best land and the saturation of the hotel offer. Consequently, a new cycle began, marked by the expansion towards larger rural lands, but with the incentive of wine tourism and the new solar train. Thus, after the pandemic, a second stage of real estate expansion towards peri-urban areas was consolidated through the promotion of more exclusive leisure services, a situation that fed back into the differential appropriation of rents; specifically, “tourism monopoly rents”. In fact, data proving the described scenario are shown, based on the reconstruction of real estate price series and the zoning of the main urban areas of the region. It also analyzes the relative location of vineyard ventures, recent space building infrastructure, the real estate market and the chances of obtaining rents.